2013
DOI: 10.3136/fstr.19.97
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrocolloids on Partial Baking and Frozen Storage of Wheat Flour Chapatti

Abstract: The use of hydrocolloids in different foods systems has become more commonly applied to improve the texture and quality of baked products. Nevertheless, the effects of these compounds on partially baked frozen chapatti have not been studied. The objective of the present study was to improve the storage stability, quality and shelf life of partially baked chapatti by adding various hydrocolloids, hydroxyl propyl methylcellulose (HPMC), carboxy methylcellulose (CMC) and guar gum, followed by frozen storage for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…improved the specific volume and also reduced crumb hardness and retrogradation index (B arcenas & Rosell, 2007;B arcenas, Benedito, & Rosell, 2004). Likewise, Ahmed et al (2013) reported that HPMC, followed by CMC and GG (0.5%), improved moisture retention and the sensory characteristics in par-baked chapatti bread from whole wheat flour. Pectin (1%) maintained softer crumbs during longer periods in parbaked breads stored at 4 C or À18 C (Rosell & Santos, 2010).…”
Section: Hydrocolloids Used In Bake Off Technologiesmentioning
confidence: 87%
“…improved the specific volume and also reduced crumb hardness and retrogradation index (B arcenas & Rosell, 2007;B arcenas, Benedito, & Rosell, 2004). Likewise, Ahmed et al (2013) reported that HPMC, followed by CMC and GG (0.5%), improved moisture retention and the sensory characteristics in par-baked chapatti bread from whole wheat flour. Pectin (1%) maintained softer crumbs during longer periods in parbaked breads stored at 4 C or À18 C (Rosell & Santos, 2010).…”
Section: Hydrocolloids Used In Bake Off Technologiesmentioning
confidence: 87%
“…In other studies, the protein value among samples with or without gum had no significant difference. For example, the protein content of chapatti bread without gums, containing 0.5% HPMC or 0.5% CMC, was reported as 11.68, 11.74, and 11.71% respectively (Ahmed et al., 2013 ). Also, non‐significant ( p < .05) changes were reported for protein content among the cupcake samples prepared with different concentrations of CMC (Abdelnaby et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This reaction decreases environment hydrophobic characteristic and increases water content (Wang et al, 2019). Since hydrophilic are hydrophile and spread and stabilize water in the system, adding gum to the formulation of bakery products increase moisture in the final product (Ahmed et al, 2013). Figure 5 illustrates the SpVol for the treatments under study.…”
Section: Moisture Contentmentioning
confidence: 99%